2018
DOI: 10.1080/1364436x.2017.1419938
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the effect of worship attendance and personal prayer on spiritual well-being among 9- to 11-year-old students attending Anglican church schools in Wales

Abstract: Modelling the effect of worship attendance and personal prayer on spiritual wellbeing among 9-to 11-year-old students attending Anglican church schools in Wales This study employs a modified form of the Fisher 16-item Feeling Good, Living Life measure of spiritual wellbeing (assessing quality of relationships across four domains: self, family, nature, and God) among a sample of 1,328 students drawn from year five and year six classes within Church in Wales primary schools, alongside measures of frequency of wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The second objective of the present study was to reflect on the level of spiritual wellbeing recorded on the modified Fisher instrument by students in the Republic of Ireland, compared with the students in Wales reported by Francis, Fisher, Lankshear, and Eccles (2018). The original study in Wales reported a mean score of 63.1 with a standard deviation of 10.4.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…The second objective of the present study was to reflect on the level of spiritual wellbeing recorded on the modified Fisher instrument by students in the Republic of Ireland, compared with the students in Wales reported by Francis, Fisher, Lankshear, and Eccles (2018). The original study in Wales reported a mean score of 63.1 with a standard deviation of 10.4.…”
Section: Resultsmentioning
confidence: 95%
“…This paper set out to replicate, to build on and extend the study reported by Francis, Fisher, Lankshear, and Eccles (2018) conducted among 9-to 11-year-old students attending Anglican schools within Wales. This replication of the original work, conducted among students attending Anglican schools within the Republic of Ireland, makes four original contributions to knowledge.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations